Insights into the energy storage mechanism of hybrid supercapacitors with redox electrolytes by Electrochemical Impedance Spectroscopy. (10th February 2018) - Navalpotro, Paula; Anderson, Marc; Marcilla, Rebeca; Palma, Jesús
Abstract: Recently, new electrode materials and electrolytes for hybrid supercapacitors with enhanced performance have been extensively studied. However, the energy storage mechanism of these hybrid devices has not been assessed in detail. In this sense, Electrochemical Impedance Spectroscopy is one of the most powerful techniques to better understand the physicochemical phenomena involved in this new kind of supercapacitors. In this work, Impedance Spectroscopy was used for the first time to analyse the energy storage mechanism in supercapacitors with non-aqueous electrolytes with organic redox molecules dissolved, as a function of the frequency and bias voltage. In addition, a simple electrical model has been developed to describe the behavior of the supercapacitor with a very good correlation with the experimental results. This investigation provides useful information delving into the behavior of the devices which is fundamental for their future practical applications. Graphical abstract: